2013
DOI: 10.5665/sleep.2798
|View full text |Cite
|
Sign up to set email alerts
|

Predeployment Sleep Duration and Insomnia Symptoms as Risk Factors for New-Onset Mental Health Disorders Following Military Deployment

Abstract: Gehrman P; Seelig AD; Jacobson IG; Boyko EJ; Hooper TI; Gackstetter GD; Ulmer CS; Smith TC; for the Millennium Cohort Study Team. Predeployment sleep duration and insomnia symptoms as risk factors for new-onset mental health disorders following military deployment. 2013;36(7):1009-1018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
168
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(194 citation statements)
references
References 71 publications
18
168
3
Order By: Relevance
“…12 In the Millennium Cohort, a sample of military personnel serving since 9/11, pre-deployment short sleep duration and insomnia symptoms were predictive of new-onset post-deployment PTSD, anxiety and depression. 13 Sleep problems have also been found to predict suicide in several studies. 14,15 In veterans, sleep disturbances explained 57% of the variance in time-tosuicide in suicide completers even after adjusting for psychiatric and substance abuse symptoms.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…12 In the Millennium Cohort, a sample of military personnel serving since 9/11, pre-deployment short sleep duration and insomnia symptoms were predictive of new-onset post-deployment PTSD, anxiety and depression. 13 Sleep problems have also been found to predict suicide in several studies. 14,15 In veterans, sleep disturbances explained 57% of the variance in time-tosuicide in suicide completers even after adjusting for psychiatric and substance abuse symptoms.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…This belief is contradictory to the available scientific evidence, 18,19 and neglecting insomnia may only worsen the prognosis for those comorbid conditions. 20 Interestingly, providers were often supportive of the importance of insomnia, another important finding of this investigation. Most of the providers (80%) thought that insomnia was as important as other health concerns, and two thirds (67%) believed that treating insomnia was as important as treating sleep apnea.…”
mentioning
confidence: 92%
“…Several recent self-report studies suggested that insomnia increases the likelihood of PTSD development following trauma [60,61]. Subjective difficulty falling and staying asleep prior to deployment predicts later development of PTSD following combat exposure [12]. Both subjective and clinician-rated sleep disturbances and associated daytime difficulties predict PTSD and other internalizing disorders in National Guard troops [13].…”
Section: Rdoc Framework-based Correlates Of Trauma and Sleepmentioning
confidence: 99%
“…Furthermore, recent research has demonstrated that sleep problems may play an etiological role in the development of PTSD [12,13]. By shifting the focus of research efforts towards the mechanisms of sleep and PTSD symptomatology, we may better understand the underlying constructs, as well as inform innovative and ideographically targeted treatments [14].…”
Section: Introductionmentioning
confidence: 99%